Steady States of Sheared Active Nematics (Advances in Applied Mathematics and Mechanics, 2014)
A continuum hydrodynamic model has been used to characterize flowingactive nematics. The behavior of such a system subjected to aweak steady shear is analyzed. We explore the director structures andflow behaviors of the system in flow-aligning and flow tumbling regimes.Combining asymptotic analysis and numerical simulations, we extend previousstudies to give a complete characterization of the steady states for both contractile andextensile particles in flow-aligning and flow-tumbling regimes.  Anotherkey prediction of this work is the role of the system size on the steadystates of an active nematic system: if the system size is small, the velocityand the director angle files for both flow-tumbling contractile and extensilesystems are similar to those of passive nematics; if the system is big, thevelocity and the director angle files for flow-aligning contractile systemsand tumbling extensile systems are akin to sheared passive cholesterics whilethey are oscillatory for flow-aligning extensile and tumbling contractile systems.